2013
DOI: 10.1103/physrevstper.9.020119
|View full text |Cite
|
Sign up to set email alerts
|

Analytic framework for students’ use of mathematics in upper-division physics

Abstract: Many students in upper-division physics courses struggle with the mathematically sophisticated tools and techniques that are required for advanced physics content. We have developed an analytical framework to assist instructors and researchers in characterizing students' difficulties with specific mathematical tools when solving the long and complex problems that are characteristic of upper division. In this paper, we present this framework, including its motivation and development. We also describe an applica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
121
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(131 citation statements)
references
References 26 publications
10
121
0
Order By: Relevance
“…In this section we describe the ACER framework [3] and how it was used in this research. We also discuss the context of our study, including an overview of the two questions students were asked to solve.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section we describe the ACER framework [3] and how it was used in this research. We also discuss the context of our study, including an overview of the two questions students were asked to solve.…”
Section: Methodsmentioning
confidence: 99%
“…The use of math in physics is vastly different than its use in mathematics [2]. ACER was designed as an analytic framework to describe how students use various mathematical tools in advanced physics contexts [3]. In this study we use ACER to both design and analyze mathematically rich questions in the context of quantum mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…For upper-division physics courses, Wilcox et al have proposed the ACER framework 'to guide and structure investigations of students' difficulties with the sophisticated mathematical tools used in their physics classes.' [11] In this framework, students must activate the appropriate mathematical tool in addition to constructing a model, executing the mathematics, and then reflecting on results.…”
Section: A Background and Relevant Prior Workmentioning
confidence: 99%
“…Thus, students are expected to have a good grasp of at least basic mathematical skills in order for them to be able to apply these skills during problem solving. There has been little research on the mathematical aspect of physics problem solving [5,[9][10][11]. Previous studies have shown a positive correlation between student difficulties with physics concepts and those with either the mathematics concepts, application of those concepts, or the representations used to connect the mathematics and the physics.…”
Section: Introductionmentioning
confidence: 99%
“…The four steps include (i) modeling the physical system to mathematical representation, (ii) processing the mathematical operations, (iii) interpreting the results of the mathematical operations in terms of the physical system, and (iv) evaluating the results to justify the initial modeling. Wilcox and colleagues refined Redish's model to explain students'use of mathematics in upper-division physics [10]. Their framework also contains four elements in the problem-solving process including activation of mathematical tools, construction of mathematical models, execution of the mathematics, and reflection on the results (ACER).…”
Section: Introductionmentioning
confidence: 99%